Disputed questions in theology and the philosophy of religion - Hick, John, 1922-2012 (Yale University Press, 1993)
When medieval theologians wrote their Quaestiones Disputatae, the disputed questions concerned relatively peripheral topics, for most Christians agreed on all of the most basic matters. But today even the most central issues in Christianity are controversial, and Christian discourse itself is part of the wider dialogue that includes all the great religious and philosophical traditions of the world.